2012
DOI: 10.5539/ijbm.v7n7p172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Audit Committee’s Effectiveness on Dividend Payout Policy: Evidence from the Jordanian Firms

Abstract: This paper examines the possible association between audit committee's effectiveness and Jordanian industrial public shareholding companies' dividend payout policy. Data was collected through two sources; first, a questionnaire survey was distributed to 63 listed Jordanian firms to collect data concerning degrees of audit committees' effectiveness. Second, data concerning dividends payout policies was collected from published data for Jordanian firms. The results of the multiple regressions indicated that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…The audit ISSN 2164-4063 2014 www.macrothink.org/ijld committee performs many of the main functions; while the main responsibility of the audit committee is to supervise and manage the process of financial reporting (Klein, 2002). In practice, Nimer, Warrad and Khuraisat (2012) found that the performance of the audit committees in Jordanian listed firms seem to be poor and ineffective due to the constraints on audit committees' members' work and also the weak independence of their members as their results have shown. They also showed that most of the audit committees' members have close relationships with the members of board of directors and the top management of the firms.…”
Section: The Relationship Between Audit Committee and Accounting Consmentioning
confidence: 97%
“…The audit ISSN 2164-4063 2014 www.macrothink.org/ijld committee performs many of the main functions; while the main responsibility of the audit committee is to supervise and manage the process of financial reporting (Klein, 2002). In practice, Nimer, Warrad and Khuraisat (2012) found that the performance of the audit committees in Jordanian listed firms seem to be poor and ineffective due to the constraints on audit committees' members' work and also the weak independence of their members as their results have shown. They also showed that most of the audit committees' members have close relationships with the members of board of directors and the top management of the firms.…”
Section: The Relationship Between Audit Committee and Accounting Consmentioning
confidence: 97%
“…Regarding the results of the conducted studies, (Nimer et al, 2012) indicated that there is no relationship between the effectiveness of the external audit committee and the dividend decision in the Jordanian industrial companies. This is rather than using the survey list method to assess the effectiveness of audit committees, as we find on the other hand the results of a study indicating a relationship between the effectiveness of the external audit committee and the dividend decision in Egyptian industrial companies.…”
Section: Governance Mechanisms and Dividend Decisionmentioning
confidence: 96%
“…Namun, ukuran komite audit belum dapat menjelaskan pengaruhnya terhadap kebijakan dividen di Indonesia. Nimer et al (2012) menyebutkan komite audit harus patuh dan tegas melaksanakan tanggung jawabnya sehingga tidak melakukan kegiatan menyimpang yang menghilangkan sikap independensinya. Selain keberadaannya, kurangnya kepatuhan dan efektivitas komite audit menjadi alasan insignifikan hasil pengujian.…”
Section: Pembahasanunclassified